Investigating the link between transformational leadership style on succession planning program in national secondary schools in Seremban district, Malaysia - Armugam, Banu; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Hamzah, Siti Raba'ah (Human Resource Management Academic Research Society, 2019)
School organizations are facing with numerous challenges especially on the practice of succession planning program including identifying future leaders, retaining and developing employees’ leadership skills, key positions not filled by talented leaders and high turnover rates. This study utilized “Seven-Pointed Star Model” for succession planning and management program as it has been used in practice extensively. Moreover, succession planning needs to be linked to other components such as transformational leadership style to be successful. Transformational leadership style consists of four domains such as individualised influence, inspiration motivation, idealize influence and intellectual stimulation were used. This study aims to examine the level of transformational leadership style and succession planning as well as the relationship between them and the contribution of transformational leadership style on succession planning among principals in national secondary schools, Seremban. It is conducted using quantitative cross-sectional survey questionnaire method. The instruments used were Effective Succession Planning & Management (SP&M) and adapted version of the Multifactor Leadership Questionnaire. The obtained data was processed using SPSS program and were analysed on descriptive, correlational and regression. The findings show transformational leadership style portrays at high level of practice (M=3.86, SD=0,530) while succession planning indicates at moderate level (M=3.40, SD=0.758) and has a significant positive relationship with transformational leadership style (r = 0.527, p<0.05) in the organization of the studied population. The multiple regression analysis results revealed that idealised influence (ß=.222, p<0.05) is the main predictor on succession planning as perceived by subject leaders. Conclusively the succession planning is influenced by leadership characteristic as perceived by followers. The implication of the study is that the school principals should be able to provide a great characteristic style and always ensure their high leadership performance is significantly related to succession planning.